2020
DOI: 10.1186/s40478-020-00947-0
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of homeostatic microglial phenotype in CSF1R-related Leukoencephalopathy

Abstract: Microglia are resident macrophages of the central nervous system, and their unique molecular signature is dependent upon CSF-1 signaling. Previous studies have demonstrated the importance of CSF-1R in survival and development of microglia in animal models, but the findings are of uncertain relevance to understanding the influence of CSF-1R on microglia in humans. Hereditary diffuse leukoencephalopathy with spheroids (HDLS) [also known as adult onset leukoencephalopathy with spheroids and pigmented glia (ALSP)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 49 publications
10
79
0
Order By: Relevance
“… 74 Deep cortical layers could be more vulnerable than superficial cortical layers in patients with CSF1R -related leukoencephalopathy. 75 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Deep cortical layers could be more vulnerable than superficial cortical layers in patients with CSF1R -related leukoencephalopathy. 75 …”
Section: Discussionmentioning
confidence: 99%
“…74 Deep cortical layers could be more vulnerable than superficial cortical layers in patients with CSF1R-related leukoencephalopathy. 75 CSF1R-related leukoencephalopathy is a rare but rapidly progressive neurodegenerative disease. A clinical diagnosis of CSF1R-related leukoencephalopathy should be considered International Journal of General Medicine 2020:13 submit your manuscript | www.dovepress.com…”
Section: Dovepressmentioning
confidence: 99%
“…Upregulation of Mif expression has been implicated in the activation of microglial‐mediated inflammatory processes and has recently been proposed to be a biomarker of Alzheimer’s disease (Zhang et al , 2016, 2019). Furthermore, MIF expression has been demonstrated to enhance tight junction breakdown and blood–brain barrier permeability in stroke (Liu et al , 2018), and MIF‐mediated processes are reported to be significantly altered in ALSP frontal cortex white matter (Kempthorne et al , 2020). The restriction of these transcriptional changes in TJ components , Il34 and Mif to Csf‐1r +/− endothelial cells responding to soluble factors from Csf‐1r +/− microglia indicates CSF‐1R as a key regulator of microglial‐endothelial crosstalk.…”
Section: Resultsmentioning
confidence: 99%
“…Microglia are adapted to the CNS microenvironment and express specific gene signatures ( P2ry12 , Tmem119 and SiglecH ) in order to perform tissue-specific functions [ 39 ]. In CSF1R -related leukoencephalopathy, loss of Iba1 + /P2ry12 + microglia were observed in vulnerable cerebral white matter, but not in unaffected grey matter [ 40 ]. Microglia exhibit a distinct morphology with narrow cytoplasm and fragmented processes containing beaded structures, differing from activated microglia that are characterized with retracted processes and enlarged cytoplasm in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that long-term microglial depletion leads to monocyte colonization of the empty niche [ 44 ]. The functional role of infiltrating monocyte-derived cells in CSF1R -related leukoencephalopathy remains to be investigated [ 40 ].…”
Section: Introductionmentioning
confidence: 99%